Roles of an upper-body compression garment on athletic performances - Hooper, D. R.; Dulkis, L. L.; Secola, P. J.; Holtzum, G.; Harper, S. P.; Kalkowski, R. J.; Comstock, B. A.; Szivak, T. K.; Flanagan, S. D.; Looney, D. P.; DuPont, W. H.; Maresh, C. M.; et al. (The Journal of Strength and Conditioning Research, 2015)
Compression garments (CGs) have been previously shown to enhance proprioception; however, this benefit has not been previously shown to transfer to improved performance in sports skills. The purpose of this study was to assess whether enhanced proprioception and comfort can be manifested in improved sports performance of high-level athletes. Eleven Division I collegiate pitchers (age: 21.0 ± 2.9 years; height: 181.0 ± 4.6 cm; weight: 89.0 ± 13.0 kg; body fat: 12.0 ± 4.1%) and 10 Division I collegiate golfers (age: 20.0 ± 1.3 years; height: 178.1 ± 3.9 cm; weight: 76.4 ± 8.3 kg; body fat: 11.8 ± 2.6%) participated in the study. A counterbalanced within-group design was used. Subjects performed the respective baseball or golf protocol wearing either typical noncompressive (NC) or the experimental CG. Golfers participated in an assessment of driving distance and accuracy, as well as approach shot, chipping, and putting accuracy. Pitchers were assessed for fastball accuracy and velocity. In pitchers, there was a significant (p = 0.05) improvement in fastball accuracy (NC: 0.30 ± 0.04 vs. CG: 0.21 ± 0.07 cm). There were no differences in pitching velocity. In golfers, there were significant (p = 0.05) improvements in driving accuracy (NC: 86.7 ± 30.6 vs. CG: 68.9 ± 18.5 feet), as well as approach shot accuracy (NC: 26.6 ± 11.9 vs. CG: 22.1 ± 8.2 feet) and chipping accuracy (NC: 2.9 ± 0.6 vs. CG: 2.3 ± 0.6 inch). There was also a significant (p = 0.05) increase in comfort for the golfers (NC: 3.7 ± 0.8 vs. CG: 4.5 ± 1.0). These results demonstrate that comfort and performance can be improved with the use of CGs in high-level athletes being most likely mediated by improved proprioceptive cues during upper-body movements.